Platinum Nanoparticles: The Potential Antioxidant in the Human Lung Cancer Cells - Noor Akmal Shareela Ismail; Jun Xin Lee; Fatimah Yusof (Antioxidants, 2022)
Oxidative stress-related conditions associated with lung cells, specifically lung cancer, often lead to a poor prognosis. We hypothesized that platinum nanoparticles (PtNPs) can play a role in reversing oxidative stress in human lung adenocarcinoma A549 epithelial lung cell lines. Hydrogen peroxide (H2O2) was used to induce oxidative stress in cells, and the ability of PtNPs to lower the oxidative stress in the H2O2 treated epithelial lung cell line was determined. The differential capacity of PtNPs to remove H2O2 was studied through cell viability, nanoparticle uptake, DNA damage, ROS production, and antioxidant enzymes (superoxide dismutase, glutathione peroxidase, and catalase). Results indicated that a higher concentration of PtNPs exhibited a higher antioxidant capacity and was able to reduce DNA damage and quench ROS production in the presence of 350 µM H2O2. All antioxidant enzymes’ activities also increased in the PtNPs treatment. Our data suggested that PtNPs could be a promising antioxidant in the treatment of lung cancer.